Genetically-mediated Grey and White Matter Alteration in Normal Elderly Individuals with the CLU-C Allele Gene - Qiu, Lihua; He, Yong; Tang, Hehan; Zhou, Yi; Wang, Jinhong; Zhang, Weiwei; Chen, Guangxiang; Zhao, Fei; Ouyang, Tingxue; Ju, Bin; Li, Zhengyan; Wang, Lanlan; et al. (Current Alzheimer Research, 2016)
Background: Several genome-wide association studies have found that the rs11136000 polymorphism of the C allele (CLU-C) is associated with the risk for developing late-onset Alzheimer’s disease (LOAD). However, the effects of the CLU-C/C genotype on brain structure, including gray and white matter, are not adequately understood. Objectives: We aimed to clarify the gray matter and white matter integrity changes in non-demented ageing individuals with the AD risk gene of the rs11136000 polymorphism of the C allele (CLU-C) and the correlation with cognitive performance. Methods: Voxel-based analysis was used to compare the differences in high-resolution structural T1 and diffusion tensor imaging data between 31 CLU-C/C and 15 non-CLU-C/C carriers in nondemented older adults. Results: Compared to non-CLU-C/C carriers, CLU-C homozygotes showed a reduced gray matter concentration (GMC) in the left parahippocampal gyrus, right middle frontal and temporal middle gyri, increased GMC in the left middle frontal and right fusiform gyri and increased gray matter volume (GMV) in the left middle frontal gyrus (P < 0.001). Decreased fractional anisotropy (FA) in the sub-gyral white matter of the left external capsule and left anterior cingulate and increased FA in the sub-gyral white matter of the left temporal lobe were also found in CLU-C/C genotype carriers. Moreover, the FA value in the left external capsule correlated with several cognitive measures. Conclusion: Our findings provide further evidence for the CLU risk variant as a candidate gene for AD and may serve as a pre-clinical neuroimaging phenotype of late-onset AD.
Keywords: neuroimaging